Protein Synthesis Directed by Encephalomyocarditis Virus RNA: Properties of a Transfer RNA-Dependent System - Aviv, H. (1971)
Small amounts of encephalomyocarditis virus RNA direct a 50-fold increase in amino acid incorporation, in appropriately supplemented ascites tumor cell extracts, under conditions that give rise to authentic viral polypeptides. Incorporation in these crude extracts has a novel characteristic, namely, that it is almost entirely dependent upon the addition of exogenous tRNA. Further, this incorporation is restricted in that tRNA derived from ascites tumor cells or from rat liver permits translation of viral RNA, whereas tRNA from yeast or Escherichia coli does not. These translational barriers are due, at least in part, to an incompatibility between the tRNA of yeast and E. coli and the aminoacyl-tRNA synthetases of the ascites tumor cell. A more extensive basis for this incompatibility is suggested, however, by the failure of the E. coli aminoacyl-tRNA synthetases to restore viral RNA-directed protein synthesis in the presence of tRNA from E. coli, although the coli synthetases fully restore the poly(U)-directed synthesis of polyphenyl-alanine. The possible role that unique or favored codon classes might play in this restriction is considered, together with the implications of the observed requirement for tRNA.